Minaidou, Despo - (:unkn) unknown (My University, 2026)
Special Teaching Staff position at Department of Rehabilitation Sciences-Speech Language Therapy/Pathology Program, Cyprus University of Technology, Limassol, Cyprus. Responsible for setting up the Clinical Practicums for the undergraduate program of Speech language Therapy/Pathology of the department. Additionally responsible for executing the courses Ethics & Counseling in Speech Language Therapy & Communication disorders, Introduction to clinical practice, Introduction to Speech Therapy, Topics in Speech therapy, Clinical Practicum I, II & III and the placements for the Clinical Practicum-Clinical Externships (5 months). Additional responsibilities include coordination of the University Rehabilitation Clinic, the caseload and the clinical supervisors.